“You could See it [the Past] in your Mind”: What Impact might Living History Performance Have on the Historical Consciousness of Young People? - Ceri Jones (EXARC Journal)
2012 OpenArch meeting at Foteviken (SE). Living history is used as part of a range of interpretive techniques to help young people experience and learn about the past at museums and historic sites (Samuel 1994). Although the benefits of bringing the past to life have been enthusiastically supported by costumed interpreters, museum and history educators (Fairley 1977; Turner-Bisset 2005) it was not until 2008 that a significant research project was completed into the learning potential of performance and live interpretation (Jackson and Kidd 2008). Since then, the volume of research into this topic has increased (Kostarigka 2009; Tzibazi 2012) but there are still many questions to ask, not least, how does the way in which a performance is structured or framed (Schechner 2006) affect the learning potential of living history?